Dynamic contrast enhanced MRI monitoring of primary proton and carbon ion irradiation of prostate cancer using a novel hypofractionated raster scan technique. Issue 2 (August 2016) - Bonekamp, David; Wolf, Maya B.; Edler, Christopher; Katayama, Sonja; Schlemmer, Heinz-Peter; Herfarth, Klaus; Röthke, Matthias
Abstract: Purpose: To characterize parametric changes measured by sequential dynamic contrast enhanced perfusion MRI (DCE-MRI) during primary proton and carbon ion irradiation of prostate cancer using a novel hypofractionated raster scan technique to determine the potential of pharmacokinetic analysis for monitoring treatment effects of this novel irradiation scheme. Materials and methods: Ninety-two patients were evaluated prospectively with DCE-MRI at baseline, day 10 during therapy, and 6 weeks, 6 months and 18 months after treatment completion. After motion correction and co-registration to morphological T2-weighted images, tumors and normal appearing contralateral parenchyma (NACP) were segmented manually on T2W images and ROI statistics calculated for pharmacokinetic parameters K trans, k ep and v e using the standard Tofts model. Results: The volume transfer constant ( K trans, p  < 0.001/ p  = 0.010) and the leakage space partial volume ( v e, p  < 0.001/ p  = 0.005) showed a statistically significant increase during therapy with protons and carbon ions, respectively. Parametric increases occurred only in patients naive to antihormonal therapy (AHT), and were maximal 10 days after the begining of treatment. The rate constant ( k ep ) showed a significant increase only for proton, but not for carbon irradiation ( p  = 0.021). Statistically significant differences between PC and NACP were observed for all parameters ( p  < 0.001). AHT naïve patients with persistent PSA elevation above 1 ng/ml at 12 months experienced statistically significant elevation of K trans and v e compared to those with PSA suppression ( p  = 0.04/ p  = 0.023). Conclusion: DCE parametric changes following ion particle irradiation of the prostate have not been previously reported. Their development into potential non-invasive imaging biomarkers for assessment of treatment response and efficacy is expected to be aided by the data on the magnitude and temporal evolution of parametric responses of cancer and normal tissue during and after therapy presented here, especially the changes of K trans and v e during therapy and their different measurement levels within tumors and in normal appearing contralateral tissue.